Suggestions on cyber security talents cultivation - Hong-li ZHANG; Hai-ning YU; Jian-hong ZHAI; Xiang-zhan YU (网络与信息安全学报)
Talent competition is the core content of cyber security competition. Firstly, the definitions and characteristics of cyber security were introduced. Then, the development status of international cyber security talents cultivation were analyzed, and the main problems existing in cyber security talents cultivation were pointed out. Finally, based on national significant strategy, suggestions on cyber security talents cultivation to explore a sophisticated architecture were proposed, which refer to the national overall planning, academic education, vocational training and certification, genius discovery and cultivation.